Studi Penggunaan Antihipertensi Golongan Angiotensin Reseptor Blocker (ARB) pada Pasien Chronic Kidney Disease (Penelitian dilakukan di RS Universitas Muhammadiyah Malang) - Nurfausiah, Nurfausiah; Hasmono, Didik; Kusumaningtyas, Atika Putri; Syifa', Nailis (Jurnal Farmasi Malahayati (JFM), 2024)
Hypertension and chronic kidney disease (CKD) are interrelated pathophysiological conditions, where sustained hypertension can lead the deterioration of renal function, and progressive deterioration of renal function can conversely result in poorer blood pressure (BP) control. Antihypertensives are given to CKD patients with the goal of lowering their blood pressure to < 140 mmHg and preventing harm to other organs. Angiotensin Receptor Blockers (ARB) are one of the first line of therapy used to reduce blood pressure in CKD patients. The research purpose was to determine the pattern of ARB regarding the type, dosage form, combination, and route of the group given to CKD patients at UMM’s General Hospital. Research was conducted in observational research with a descriptive nature and retrospective data collection on the health medical record of CKD with period January – Desember 2022. Results of the research showed that patients who met the inclusion criteria amounted to 25 patients using ARB antihypertensive therapy, the highest number of gender 52% male and 48% female, at the age of 46-55 years. The most common single use was Candesartan (1x16mg)po (5%) 2 patients, the most common combination II was Candesartan (1x16mg)po + Furosemide (3x40mg) iv 7 patients (18%), the most common combination III was Candesartan (1x16mg)po + Amlodipine (1x10mg)v + Furosemide (3x40mg)iv, the most common combination IV was Candesartan (1x16mg)po + Amlodipine (1x10mg)po + Clonidine (3x0.15mg)po + Furosemide (3x40mg)iv. There was a switch pattern as many as 13 samples (52%). Most patients met the blood pressure target at ≤ 140 mmHg.